2018
DOI: 10.17765/1983-1870.2018v11n2p267-276
|View full text |Cite
|
Sign up to set email alerts
|

Estresse E Estratégias De Enfrentamento Da Fissura Labiopalatina Por Pré-Adolescentes

Abstract: A fissura labiopalatina (FLP) é uma malformação que gera necessidade de assistência ao seu portador desde seu nascimento até o final da adolescência. Neste período, diversas situações estressantes relacionadas ao tratamento podem ocorrer. Este estudo analisou os principais estressores relacionados à FLP e seu tratamento e seu enfrentamento/coping. A amostra foi composta por 22 pré-adolescentes com idade de 9-11 anos, em tratamento desde o nascimento em um centro de assistência especializado. O Responses to Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…It is believed that these results are a consequence of better socioeconomic conditions of the CL±P individuals, since most received two to three minimum wages, in contrast to the controls that received up to one minimum wage. A study conducted in Paraná, another Brazilian state [8], showed family income of the CL±P individuals in this wage range. In other studies, families of patients with craniofacial anomalies received between one and two minimum wages [9,10].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is believed that these results are a consequence of better socioeconomic conditions of the CL±P individuals, since most received two to three minimum wages, in contrast to the controls that received up to one minimum wage. A study conducted in Paraná, another Brazilian state [8], showed family income of the CL±P individuals in this wage range. In other studies, families of patients with craniofacial anomalies received between one and two minimum wages [9,10].…”
Section: Discussionmentioning
confidence: 86%
“…In other studies, families of patients with craniofacial anomalies received between one and two minimum wages [9,10]. In low-income countries, it was observed that the CL±P patients had an even lower socioeconomic level, up to a minimum wage [8,11] . In a multivariate logistic regression analysis, other risk factors were associated with low economic status such as region of birth, home delivery or delivery in a publicly funded hospital, father's or mother's family history background and prenatal diet [7].…”
Section: Discussionmentioning
confidence: 94%
“…In this context, the adaptive process is pointed out as a coping strategy that allows the individual to face their choices and is associated with the support offered. 10 …”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the choice of romantic partner, although there was an influence on the view of oneself and others in this process. 10 …”
Section: Introductionmentioning
confidence: 99%
“…A fissura labiopalatina, também conhecida como fenda labiopalatal ou lábio leporino, é uma abertura na região do lábio e/ou uma fenda no palato que resulta da união incompleta dos tecidos da face durante o desenvolvimento pré-natal. A fenda pode situar-se em um dos lados, em ambos os lados ou ao centro; e também pode estar acompanhada de uma abertura na gengiva superior, afetando lábios, nariz, região alveolar e palato (Cunha et al, 2019;Ribeiro & Enumo, 2018).…”
Section: Introductionunclassified